The Archbishop and the Marquis. An Attempt of Lordship with Aristocratic Leadership in Milan (1277-1282) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
The history of Milan between 1277 and 1295 is normally summed up in the formula, now considered too simple, of the ‘lordship of Ottone Visconti’. The almost exclusive attention to the role of the archbishop led to the neglect of the liveliness of the political struggle in Milan in the late XIII century. Between 1278 and 1282 some families of the Milanese aristocracy sought to conquer the rule of the city by delivering it to marquis Guglielmo VII of Monferrato. The failure of the attempt opened the way to the return to the power of the Popolo of Milan, with the support of the Archbishop Ottone.DOI 10.17464/9788867742714
Keywords: Milan; Guglielmo VII of Monferrato; commune; lordship